PREDICTION OF THE THERMODYNAMIC PROPERTIES OF AQUEOUS METAL COMPLEXES TO 1000OC AND 5 KB - Sverjensky D.A.; Shock E.L.; Helgeson H.C. (My University, 1997)
A large number of aqueous metal complexes contribute significantly to hydrothermal, metamorphic, and magmatic processes in the crust of the Earth. Nevertheless, relatively few thermodynamic data other than dissociation constants (K) for a few dozen of these complexes have been determined experimentally at elevated temperatures and pressures. The calculations summarized below are intended to supplement these experimental data by providing interim predictions of the thermodynamic properties of supercritical aqueous metal complexes using the revised HKF (Helgeson et al., 1981) equations of state for aqueous species (Tanger and Helgeson, 1988; Shock et al., 1992) and correlations among equations of state parameters and standard partial molal properties at 25°C and 1 bar (Shock and Helgeson, 1988, 1990; Shock et al., 1989). These equations and correlations permit retrieval of the conventional standard partial molal entropies (S0), volumes (V0), and heat capacities (C0P) of aqueous metal complexes at 25°C and 1 bar from published values of log K in the supercritical region and the limited number of experimental dissociation constants available in the literature over relatively short ranges of elevated temperature at PSAT (PSAT and SAT are used in the present communication to refer to pressures corresponding to liquid-vapor equilibrium for the system H2O, except at temperatures <100°C, where they refer to the reference pressure of 1 bar). The standard partial molal properties computed in this way can then be used to generate corresponding values of ΔS0, ΔV0, and ΔC0P of association, which for similar complexes correlate linearly with S0, V0, andC0P , respectively, of the constituent cations and ligands at 25°C and 1 bar. Generalizing these correlations and combining them with the equations of state permits prediction of the temperature and pressure dependence of log K and other thermodynamic properties of a large number of aqueous metal complexes. As a consequence, it is possible to retrieve values of log K at 25°C and 1 bar from the results of hydrothermal experiments at higher temperatures and pressures or to predict values of log K at hydrothermal conditions when no experimental data are available at temperatures and pressures above 25°C and 1 bar. Such predictions can be made for temperatures and pressures from 0°C and 1 bar to 1000°C and 5000 bars.